Análise de uma rede sem fio utilizando a metodologia de site survey como suporte ao projeto de reestruturação da FADESP - OLIVEIRA, Anderson Costa Novaes de (2020)
In a wireless networking project some factors must be taken into account, such as equipments that can cause interferences, other networks that already exist which can compete with the network channel that will be deployed and the positioning of access points, in order to ensure satisfactory coverage of the radio frequency signal. Thus, the objective of the present work is to show the characteristics of a wireless network and its IEEE 802.11 standards, approaching good practices for its implementation in a satisfactory way. In this sense, an existing wireless network will be analyzed by studying its characteristics, and its problems will be presented. For this, the methodology of the site survey will be used, which allows the inspection of a wireless network. The software used was the Ekahau HeatMapper, that after uploading the plant of the local, shows us where the access points are located, the areas with and without coverage, and various convenient informations to the deployment of the network. The detection of the signal and analysis of its loss, channel attenuations and channel superposition was performed by the software InSSIDer. Then, after these studies, a proposal for wireless network restructuring will be presented with the aim it has its best performance and better possible use by its users.